Dampak Kompetensi Terhadap Kinerja Dimediasi Kepuasan Kerja Guru - Wadi, Ariance Arian; Ibrahim, Muhdi B. Hi.; Pongtiku, Arry (Public Policy, 2023)
The objective of this study was to determine and analyze the direct and indirect influence of teacher competence on teacher performance through job satisfaction in several public secondary schools in Jayapura City, Papua Province. The research was conducted by sampling 145 civil servant teachers out of 331 civil servant teachers in 6 public high schools, using a deliberation/criteria technique. Data were collected through surveys and questionnaires, with a participation rate of 120 questionnaires (83%) returned, which were referred to as respondents. The analysis was performed using path analysis with the assistance of SmartPLS software version 3.0. The results of the analysis indicated that: 1) teacher competence had a positive and significant direct influence on teacher performance; 2) teacher competence had a positive and significant direct influence on job satisfaction; 3) job satisfaction had a positive and significant direct influence on teacher performance; and 4) job satisfaction mediated the positive and significant relationship between teacher competence and teacher performance.